KIAI'S SITUATIONAL LEADERSHIP STYLE IN FOSTERING SANTRI SPIRITUAL INTELLIGENCE - Muflihah, Ety; Trisnamansyah, Sutaryat; Sauri, Sofyan; Hanafiah, Hanafiah (Universitas Suryakancana, 2021)
The existence of a kiai as the leader of the pesantren is very decisive in the activities of mobilizing or motivating the members of the pesantren he leads, the kiai must be able to take actions that are always directed at achieving the goals of the pesantren organization. From here comes a leadership style that must be used as an appropriate strategy for running a pesantren organization, especially in terms of fostering the spiritual intelligence of its students. The Spiritual Intelligence (SQ) that must be possessed by students is the intelligence to place the attitudes and behavior of students who are able to implement and practice the knowledge of religion and the values contained in religion in accordance with Allah's orders and the Example of Rosululloh SAW. Spiritual intelligence (SQ) is needed to judge that one's actions or way of life are more meaningful than others. One of the leadership models that can be adopted by kiai is situational leadership whose implementation is tailored to the situation at hand. Hersey and Blanchard (1982: 180) say